ISTITSNA’ IN SURAH AL-AN’AM: MEANINGS AND ITS IMPLICATION - Muzdalifah, Zahrotul (Arabic Education Department, Islamic Studies Faculty, University Muhammadiyah of Malang, 2019)
This research aimed to describe the type and functions of istitsna? in Surah al-An?am, the meanings of ?adawat istitsna? and the implication for Arabic teaching and learning. The research design is descriptive qualitative. The result of this research, istisna? phrases in Surah al-An?am based on type and function, those are istitsna? muttashil which function is li takhsis, istitsna? munqathi' which function is li istidrak and istisna? 'mufarragh which function is li hasr. The ?adawat isttisna' is not always meaningless